GAMBARAN KEPATUHAN PERAWAT TERHADAP PENERAPAN UNIVERSAL PRECAUTION (STUDI DI RSUD UNGARAN) - Raditya Noriski; Septo Pawelas Arso; Rani Tyas Budiyanti (Jurnal Kesehatan Masyarakat (Undip), 2020)
Universal Precaution (UP) is a program created by the Centers for Disease Control and Prevention (CDC) that aims to reduce the risk of transmission of pathogens through blood and body fluids. In Indonesia, this is regulated in the Minister of Health Regulation No. 27 of 2017 concerning infection prevention and control programs in health care facilities. But in its application in Ungaran Regional Hospital is still not optimal because there are still several cases of Stick Injury. In theory, there are several factors associated with the level of compliance. The purpose of this study was to determine the description of nurse approval in implementing Universal Precaution in Ungaran District Hospital. This research is a quantitative study using a cross sectional study with a sample of 96 respondents. The results of this study indicate that most nurses have complied with UP. Associated with hospitals to conduct routine inspections and sudden inspections to verify nurses while working.